1971
DOI: 10.1136/bmj.2.5759.428
|View full text |Cite
|
Sign up to set email alerts
|

Serum Transaminases during Salicylate Therapy

Abstract: SummaryIn 8 out of 32 juvenile patients suffering from chronic polyarthritis and in one patient with dermatomyositis, raised transaminase levels were found; the salicylate level was above 35 mg/100 ml in all except one. Reduction in the salicylate level led to a prompt fall in the serum transaminases. Despite a rise in alkaline phosphatase in three cases there was no other evidence of liver dysfunction in the children. Only one of the adults showed a rise in transaminase levels, and she had mild cirrhosis. Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1973
1973
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…The present investigation suggests, to the contrary, that disturbances of liver function occur regularly in patients with JRA treated with salicylates in doses sufficient to raise serum levels above 25 mg/100 ml. These data confirm and extend the observations of Manso et aZ(5) that a majority of patients, with or without evidence of acute rheumatic fever, developed elevations of SGOT and SGPT 6 to 32 days after beginning a course of salicylates, and the report of Russell et a1 (6) of elevated serum transaminase levels in juvenile patients with chronic polyarthritis and high serum salicylate levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The present investigation suggests, to the contrary, that disturbances of liver function occur regularly in patients with JRA treated with salicylates in doses sufficient to raise serum levels above 25 mg/100 ml. These data confirm and extend the observations of Manso et aZ(5) that a majority of patients, with or without evidence of acute rheumatic fever, developed elevations of SGOT and SGPT 6 to 32 days after beginning a course of salicylates, and the report of Russell et a1 (6) of elevated serum transaminase levels in juvenile patients with chronic polyarthritis and high serum salicylate levels.…”
Section: Discussionsupporting
confidence: 90%
“…More than half of the patients studied, both patients with possible rheumatic fever and those without evidence of rheumatic disease, developed elevations of one or both enzymes. Recently Russell et al (6) reported transient elevations of serum transaminase levels in 8 of 32 juvenile patients suffering from chronic poly-arthritis and in 1 patient with dermatomyositis. These abnormalities were reversibly associated with salicylate therapy; the serum salicylate level was greater than 35 mg/100 ml in all cases except one.…”
mentioning
confidence: 99%
“…In one series of 32 children with JRA, elevated transaminase levels were found only with salicylate concentrations greater than 35 mg/dl (6). In another study of 6 adults and children with JRA, abnormal transaminase concentrations appeared only with salicylate concentrations greater than 25 mg/dl (7).…”
Section: Discussionmentioning
confidence: 98%
“…A recent article by Samaha and lrvin (3) in which native dsDNA was purified by means of methylated albumin Kieselguhr chromatography reports similar results. Our study and theirs support the premise that antidsDNA antibodies are specific for SLE and suggest that false positive tests can result from contamination of native dsDNA with dsDNA having ss regions.…”
mentioning
confidence: 63%